MAKNA MEMENUHI HUKUM TAURAT MENURUT RASUL PAULUS - Eddis Sagala (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2019)
fulfilling the law according to the Apostle Paul in Romans 13: 8-10. The research method in writing scientific papers is a qualitative method with an exegetical study approach. The results of the exegetical study of Romans 13: 8-10, the meaning of fulfilling the law is to love God, love fellow believers, not believers and the government as rulers determined by God. So that the implementation of the present day congregation is that every Christian must love God faithfully, love his neighbor as himself, love his fellow believers by not being a stumbling block to fellow believers, loving others who are not believers through friendship with them and giving sweet love to Jesus Christ for them, then loves the government as the ruler through obedience to all the rules and regulations he sets.Keywords: Meaning, Compliance, Law